PERSEPSI MASYARAKAT KODINGARENG TERHADAP PELAKSANAAN PILKADA DENGAN PASANGAN CALON TUNGGAL STUDI PADA PEMILIHAN WALIKOTA DAN WAKIL WALIKOTA MAKASSAR - Rismawati Rismawati; Hasnawi Haris; Imam Suyitno (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2019)
Abstract: The aim is to find out: 1) public knowledge about the procedures for implementing local elections in the election of the mayor and deputy mayor of Makassar. 2) the attitude of the community towards the implementation of the election with a single candidate pair in the election of the mayor and deputy mayor of Makassar. 3) the public's response to the superiority of the blank column in the election of the mayor and deputy mayor of Makassar. The research method used in this research is qualitative with a case study approach with interview and documentation data collection techniques. The population in this study was the people of Kodingareng Island, Kodingareng Village, Sangkarrang Islands District, Makassar City. A sample of 20 people was determined using a purposive sampling technique with certain considerations. The results showed that: 1) Public knowledge about the procedures for implementing regional elections in the Election of Mayor and Deputy Mayor of Makassar in Kodingareng Village, Sangkarrang Islands Subdistrict, was still lacking, this was due to the low level of political education for the community and the lack of socialization carried out by the KPU. 2) The attitude of the community towards the implementation of the pilkada with a single candidate pair in the election of the Mayor and Deputy Mayor of Makassar, Kodingareng Village, Sangkarrang Islands District in general is not agreeing and rejecting the holding of the election with one pair of candidates, this creates a negative public perception of the implementation of the election. 3) The public's response to the superiority of the blank column in the election of Mayor and Deputy Mayor of Makassar in Kodingareng Village, Sangkarrang Islands District, Makassar City is to accept, this is because there is a form of rejection of the implementation of the election with one pair of candidates by the community and the single candidate pair is considered not in accordance with people's wishes.Keywords: perception, pilkada, single candidate pair